Exposição de fibroblastos de pterígios recidivados e da cápsula de Tenon normal à triancinolona - Hata Viveiros, Magda Massae; Kitakawa, Dalton; de Carvalho, Clodomir S. C. [UNESP]; Candeias, Joao [UNESP]; Padovani, Carlos Roberto [UNESP]; Schellini, Silvana Artioli [UNESP] (Conselho Brasileiro de Oftalmologia, 2012)
Purpose: To evaluate the proliferation rate of recurrent pterygium and normal Tenon's capsule fibroblasts after exposure to triamcinolone.Methods: Explants of recurrent pterygia and normal Tenon's capsule of the same carrier were cultured. The fibroblasts were cultured and subcultured until the third passage and subsequently exposed to triamcinolone. The cell proliferation rate was evaluated 3, 6, 12 and 18 days after the exposure.Results: Fibroblasts exposed to triamcinolone had significantly lower proliferation rate (P < 0.05) compared to those not exposed, when the evaluation was performed 3, 6 and 12 days later. In the 18th day after exposure, there was a return in the proliferation rate, with statistical significance, only in the pterigyum fibroblasts.Conclusion: Both the fibroblasts from normal Tenon's capsule as from recurrent pterygia showed significantly lower proliferation rate after exposure to triamcinolone. After 18 days from the exposition, pterygium fibroblasts recovered the proliferation. The results suggested the triamcinolone might be useful as adjuvant in pterygium treatment.
Exposição de fibroblastos de pterígios recidivados e da cápsula de Tenon normal à triancinolona
Exposure of recurrent pterygium and normal Tenon's capsule fibroblasts to triamcinolone
Keywords: Pterygium/pathology; Fibroblasts/pathology; Fibroblasts/drug effects; Cell culture techniques; Cell proliferation/drug effects; Recurrence; Triamcinolone/pharmacology; In vitro